Efeitos das lagoas de tratamento de esgoto sobre seu entorno: casos no Pontal do Paranapanema - Santi, Lais Jerônimo de [UNESP] (2014)
The municipalities of Teodoro Sampaio, Maraba Paulista and Regente Feijo, like the majority of small municipalities, have the common characteristic of treat their sewage through stabilization ponds. The objective of this research is to evaluate the effects of treatment in the receiving water body and the effects on its surroundings, with the physical characterization of the sites and of the water quality. To this purpose, permeability tests and grain size in anthropogenic soils, analysis of influent organic loading and effluent ponds and the implementation of IQA index (water quality) were performed upstream, at the point of release and downstream. The results showed that soil surrounding the lagoons are sandy and permeable, and water quality, classified bad to very bad. Regarding the potential for self-purification of water bodies became evident that, after a certain distance, there is recovery of the water stream wich is visualized and confirmed by chemical analysis. The treatment by stabilization ponds is satisfactory, however the treatment efficiency can be improved through verification and correction of all operating variables and design review